Blackpatch of Clover, Cause of Slobbers Syndrome: A Review of the Disease and the Pathogen, Rhizoctonia leguminicola - Kagan, Isabelle A. (Frontiers in Veterinary Science, 2016)
Rhizoctonia leguminicola Gough and E.S. Elliott is a widely used name for the causal agent of blackpatch disease of red clover (Trifolium pratense L.). This fungal pathogen produces alkaloids (slaframine and swainsonine) that affect grazing mammals. Slaframine causes livestock to salivate profusely, and swainsonine causes neurological problems. Although the blackpatch fungus was classified as a Rhizoctonia species (phylum Basidiomycota), morphological studies have indicated that it is in the phylum Ascomycota, and sequencing data have indicated that it may be a new genus of ascomycete. The effects of the alkaloids on grazing mammals, and their biosynthetic pathways, have been extensively studied. In contrast, few studies have been done on management of the disease, which requires a greater understanding of the pathogen. Methods of disease management have included seed treatments and fungicides, but these have not been investigated since the 1950s. Searches for resistant cultivars have been limited. This review summarizes the biological effects and biosynthetic precursors of slaframine and swainsonine. Emphasis is placed on current knowledge about the epidemiology of blackpatch disease and the ecology and taxonomy of the pathogen. Possibilities for future research and disease management efforts are suggested.